2007
DOI: 10.1038/sj.eye.6703016
|View full text |Cite
|
Sign up to set email alerts
|

Uveitis associated with concurrent administration of rifabutin and lopinavir/ritonavir (Kaletra)

Abstract: retention cyst. The echographic characteristics of retained PFO have been described by Hasenfratz et al.5 Delayed display of the echo signal results in a hypoechogenic image due to slower sound conduction in PFO. The lesion presented here is unusually large. On the basis of clinical history and echographic findings, we believe this cyst is likely to contain PFO. It has had no functional effect on vision and no attempt should be made to remove it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Co-administration of rifamycin and PI leads to a reduction in the plasma concentration of IP [5]. These interactions may lead to an increased risk of TB drug toxicity [31,32], failure of HIV treatment, and potential development of drug resistance [29].…”
Section: Discussionmentioning
confidence: 99%
“…Co-administration of rifamycin and PI leads to a reduction in the plasma concentration of IP [5]. These interactions may lead to an increased risk of TB drug toxicity [31,32], failure of HIV treatment, and potential development of drug resistance [29].…”
Section: Discussionmentioning
confidence: 99%
“…Ritonavir is a potent inhibitor of CYP3A and has been demonstrated that it can exacerbate the adverse reactions of rifabutin [13,14]. Subsequently, recent guidelines have proposed the use of intermittently administered rifabutin 150 mg 3 times per week or 150 mg daily with close monitoring of adverse effects when used in the combination with ritonavir.…”
Section: Discussionmentioning
confidence: 99%
“…Coadministration of PIs and rifabutin will reduce the clearance of rifabutin 11 and increase the incidence of rifabutin toxicities, including uveitis. 12 Nelfinavir, a PI, is metabolized by multiple CYP enzymes, including CYP3A and CYP2C19. Coadministration of rifabutin with nelfinavir may increase the area under the concentration–time curve of rifabutin to 207%, compared with adminis tration of rifabutin alone.…”
Section: Discussionmentioning
confidence: 99%